Factors associated with the public's trust in physicians in the context of the Lebanese healthcare system: a qualitative study - Bashir Shaya; Nadine Al Homsi; Kevin Eid; Zeinab Haidar; Ali Khalil; Kelly Merheb; Gladys Honein-Abou Haidar; Elie A. Akl (BMC, 2019)
Abstract Background The Lebanese public perceives the physician-patient relationship as flawed. The objectives of this study are to assess factors associated with the public's trust in physicians in the context of the Lebanese healthcare system and to explore potential ways to enhance it. Methods We conducted a qualitative study based on a grounded theory methodology using semi-structured interviews with members of the Lebanese public (not restricted to patients). We selected participants through convenience and maximum variation sampling approaches. The constant comparative analysis resulted in a theoretical framework that describes the factors influencing trust in physicians. Results Participants trusted an experienced, up-to-date, graduate of a North American or Western European school, working in a reputable hospital, with a high level of diagnostic skills. The personal characteristics that improved trust were physicians who are 'non-materialistic', have a good rapport, and have sufficient encounter time with patients. Social factors that enhance trust in the physician include: being a family member, recommended by a family member, featured in mainstream media, and/or having a good reputation. Trust increased compliance, loyalty despite occasional mistakes committed, high consultation fees, and negative attitudes towards the physician's institution. Conversely, no trust led to severed therapeutic relationship and seeking second opinions. Conclusion The level of trust of members of the Lebanese public in physicians was affected by the personal characteristics of physicians, their practice or clinical skills, their interactions with the patient, finances, in addition to a number of social factors. Moreover, the level of trust had major implications on patients' interactions with their physicians.